2009
DOI: 10.1002/adsc.200800779
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable Polymer‐ and Silica‐Supported Ruthenium(II)‐Salen Bis‐pyridine Catalysts for the Asymmetric Cyclopropanation of Olefins

Abstract: Homogeneous ruthenium(II)-salen bis-pyridine complexes are known to be highly active and selective catalysts for the asymmetric cyclopropanation of terminal olefins. Here, new methods of heterogenization of these Ru-salen catalysts on polymer and porous silica supports are demonstrated for the facile recovery and recycle of these expensive catalysts. Activities, selectivities, and recyclabilities are investigated and compared to the analogous homogeneous and other supported catalysts for asymmetric cyclopropan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…The solid-supported ruthenium catalysts were easily recovered and recycled. Recycling catalysts 5a, 5b, and 6 demonstrated that the used catalysts could achieve very similar diastereoselectivities and enantioselectivities as in the initial runs, but decreased rates were observed, leading to longer reaction times [56]. For example, catalyst 5b required more than double the time of the original run to reach 95% yield in the third run (11 h vs. 5 h).…”
Section: Ru(ii)-salen Catalyzed Asymmetric Cyclopropanationmentioning
confidence: 82%
See 4 more Smart Citations
“…The solid-supported ruthenium catalysts were easily recovered and recycled. Recycling catalysts 5a, 5b, and 6 demonstrated that the used catalysts could achieve very similar diastereoselectivities and enantioselectivities as in the initial runs, but decreased rates were observed, leading to longer reaction times [56]. For example, catalyst 5b required more than double the time of the original run to reach 95% yield in the third run (11 h vs. 5 h).…”
Section: Ru(ii)-salen Catalyzed Asymmetric Cyclopropanationmentioning
confidence: 82%
“…Supported catalyst 5b stands as the most selective supported asymmetric cyclopropanation catalyst known in the literature [56]. Interestingly, the silica supported catalyst was significantly less selective than the polymer-supported catalyst 5b, despite the seemingly similar metal coordination sphere.…”
Section: Ru(ii)-salen Catalyzed Asymmetric Cyclopropanationmentioning
confidence: 98%
See 3 more Smart Citations